Plant Clinics for Improved Plant Health Systems—Malawian Plant Doctor Insights - Maureen Mildred Banda; Mariam A. T. J. Kadzamira; Noah Phiri (Plant-Environment Interactions)
ABSTRACT This study provides qualitative insights on the factors affecting the implementation of the plant clinic approach in Malawi from the viewpoint of plant doctors. Findings show that plant doctors perceive that the main benefit of plant clinics in Malawi has been the strengthening of local agricultural extension service systems in plant health disease diagnosis and pest management. The full potential of the plant clinic approach is, however, perceived as not being fully reached due to various challenges that include but are not limited to the scarcity of trained plant doctors coupled with the lack of sufficient resources to improve plant doctor mobility and to adequately access and use digital plant health resources. Some of these are being overcome through the embedding of the approach in national agricultural extension service systems and strategies, and integration with local plant health activities. For sustained implementation of plant clinics in Malawi, there is a need for continued policy, technical, and financial resources to support plant doctors to better utilize their knowledge to reach more farmers and to leverage digital technology to continuously broaden their plant health capacity through use of and access to mobile technology, digital plant health tools, and virtual plant health expert networks.